التسامح والعدالة في سيرة النبي ﷺ: نموذج معاصر للتعايش بين الأديان والثقافات: "Tolerance and Justice in the Biography of the Prophet ﷺ: A Contemporary Model for Interfaith and Cross-Cultural Coexistence (Al-Aasar, 2025)
This paper investigates the concepts of tolerance and justice as manifested in the life and practices of the Prophet Muhammad ﷺ, presenting them as essential foundations for building a just and pluralistic society. Drawing on Qur’anic injunctions, Prophetic traditions, and key historical events such as the Constitution of Medina, the research highlights how the Prophet ﷺ developed a civic framework that ensured peaceful coexistence among Muslims, Jews, Christians, and other groups within a shared social order. The study emphasizes that justice in the Prophetic model was impartial and universal, extending protection and fairness to both Muslims and non-Muslims alike, while tolerance was not merely rhetorical but implemented in concrete policies and interfaith relations.Furthermore, the research situates the Prophetic approach within the contemporary context of interreligious dialogue and global challenges, arguing that the values of tolerance and justice embodied in the Sunnah provide effective solutions to modern crises of sectarianism, cultural conflict, and violations of human dignity. The findings underscore that the Prophetic model is not a historical artifact but a timeless paradigm that continues to offer guidance for governance, human rights, and intercultural engagement in today’s world.